Characterization of the Spatial and Temporal Distribution of Fine Particulate Pollution in the Surface Layer of a Monsoon Asia Megacity: An Assessment of Personal Exposure of a High-Risk Occupational Group in Metro Manila, Philippines - Delos Reyes, Imee (Archīum Ateneo, 2020)
Metro Manila, Philippines is one of the megacities in monsoon Asia that has PM2.5 concentrations greater than guideline values, with the public utility jeepney (PUJ) as one of the identified sources contributing to fine particulate pollution in the city. The PUJ is the cheapest and most popular mode of transportation, and PUJ drivers (a high-risk occupational group) ply their routes for 10 to 12 hours a day that expose them to very high levels of particulate pollution. Thus, a series of field measurements was carried out for five weeks from 12 Nov-15 Dec 2018 in a high-traffic key site in Metro Manila to characterize the spatial and temporal distribution of fine particulate pollution, and to estimate the personal exposure of PUJ drivers to PM2.5. Real-time PM2.5 personal exposure levels of 31 drivers plying a fixed 10-km route were recorded continuously for 12 hours each sampling day for a week using seven portable samplers, yielding a total of 1061 complete circuits. Sampling results showed that the mean PM2.5 exposure concentration for all runs (weekends included) was ~38 g m-3 , a factor of four greater than the mean annual PM2.5 guideline value (10 g m-3 ) set by the World Health Organization. Spatial averaging of PM2.5 concentrations for all monitored runs along the route revealed that elevated levels of PM2.5 were consistently observed at key transportation microenvironments (TMEs) such as intersections in front of two universities, PUJ stop in front of a tricycle terminal, and the entire northbound section of the route across a shopping mall. Multiple linear regression (MLR) analysis was used to calculate β values that represent the incremental contribution of each TME to the personal exposure of PUJ drivers. Results showed the shopping mall had the highest v contribution (β = 52g m-3 ) among other TMEs, a factor of ~23 greater than the baseline value (β = 2.3g m-3 ). To ascertain the accuracy of field measurements, the seven portable PM2.5 samplers used in the study were collocated with a Beta Attenuation Monitor (BAM) for 16 days (N = 368, mean number of sampling points), showing strong linear relationship with the BAM for all seven sensors (r2 = 0.83 to 0.85; all p values < .001). The results of this study will provide valuable information on the PM2.5 exposure of this occupational group that is most exposed to particulate pollution, as well as the identification of locations of TMEs that have very high fine particulate pollution. Furthermore, the results of this study will offer quantitative evidence that is much needed by the government’s Public Utility Vehicle Modernization Plan (PUVMP), a policy program that aims to replace old PUJs with a more eco-friendly version that produces fewer particulate matter emissions.